Idiopathic hypoparathyroidism with extensive intracranial calcification in children: First report from Saudi Arabia. Issue 16 (April 2017) - Kamal, Naglaa M.; Alghamdi, Hamed A.; Halabi, Abdulrahman A.; Bakkar, Ayman A.; Algarni, Ali; Alharbi, Abdullah; Alharthi, Abdulla A.; Alharbi, Rawan A.; Sherief, Laila M.
Abstract: Rationale: Pediatric idiopathic hypoparathyroidism with extensive intracranial calcifications outside the basal ganglia (BG) is extremely rare with less than 10 cases worldwide. Patient concerns: An 11-year-old Saudi male child presented with tetany with otherwise normal neurological and other body system examination diagnoses severe hypocalcemia for differential diagnosis. Interventions: Further investigations revealed hyperphosphatemia and undetectable serum intact parathyroid hormone. Brain computed tomography revealed BG and extensive brain calcifications. He has no dysmorphic features, vitiligo, mucocuataneous manifestations, or hair loss. He had normal hemoglobin, electroencephalogram, and skeletal survey, with negative autoantibodies to alpha and omega interferons and negative genetic testing for Glial Cell Missing 2 (GCM2) and calcium-sensing receptors (CaSRs) excluding known causes of hypoparathyroidism. Outcomes: This case presents a rare entity of idiopathic hypoparathyroidism with extensive intracranial calcification, not only in BG but also outside the extrapyramidal system with normal mentality, development, pubertal achievement, and neurological examination. To our knowledge, this is the first report from Saudi Arabia in pediatrics. Lessons: Idiopathic hypoparathyroidism is a diagnosis of exclusion after ruling out all known causes of hypoparathyroidism. It is associated with BG calcifications, but extensive intracranial calcifications outside the BG are extremely rare.